Role of Transesophageal 3D Echocardiography in Adult Cor Triatriatum Diagnosis - Serra, Walter; Benatti, Giorgio; Biagi, Andrea (Acta Biomedica Atenei Parmensis, 2018)
Cor triatriatum is a very rare congenital abnormality, symptomatic during childhood;the non restrictive form is usually diagnosed as an incidental finding. We report the case of a 88 years old man referred to our hospital for elective endovascular repair of an aortic aneurysm; transthoracic cardiac bidimensional echocardiography showed an abnormal mass into the left atrium and a the diagnosis of cor triatriatum was fully made by a three dimensional transesophageal echocardiography. 3D echocardiography is an excellent noninvasive method that provides a rapid bedside diagnosis , without having to use ionizing radiation.